Correlation of instagram usage intensity, fear of missing out, and subjective well-being among university students: Hubungan antara intensitas penggunaan instagram, fear of missing out, dan kesejahteraan subjektif pada mahasiswa - Nadira Amania,; Amanda Pasca Rini,; Nindia Pratitis, (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
This study aimed to determine the correlation between Instagram usage intensity and fear of missing out on the subjective well-being of This study aimed at fifty-three university students in Surabaya are involved as respondents. Data was collected using accidental sampling and data analysis techniques using multiple linear regression. The results of the study show that there is a relationship between Instagram usage intensity and fear of missing out on subjective well-being.